An Analysis of Taboo Words in Grand Theft Auto (GTA) : San Andreas Opening and Mission 1 Game Script - Rosa Runa Nabila; Deden Novan Setiawan Nugraha (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research focuses on types and function of taboo words that used in Grand Theft Auto (GTA): San Andreas Opening and Mission 1 Game Script. The data of this research were taken from GTA: San Andreas game script. The objectives of this research are to identify the types and functions of taboo words uttered by the characters in GTA: San Andreas. The data were collected by selecting dialogues containing taboo words after watching the video and matching the game script with the video carefully. The researcher found out three types of taboo word that appeared in GTA: San Andreas. There are obscenity types, profanity types, and epithet types. Obscenity is the type with the highest number compared to other types, there are 12 data obscenity. 6 data epithets. Then, the last type is a profanity, only 3 data of profanity. Total there are 21 data that researchers found in the Grand Theft Auto (GTA): San Andreas opening and mission 1 game script.